Toxoplasma gondii: Evidence for the transmission by semen in dogs - Arantes, Tiago Pereira [UNESP]; Zanetti Lopes, Welber Daniel [UNESP]; Ferreira, Roberta Machado [UNESP]; Pinto Pieroni, Juliana S. [UNESP]; Pinto, Vanessa M. R. [UNESP]; Sakamoto, Claudio A. [UNESP]; da Costa, Alvimar Jose [UNESP] (Academic Press Inc. Elsevier B.V., 2009)
Ten male dogs were distributed into three experimental groups for infection with Toxoplasma gondii: GI three dogs inoculated with 2.0 x 10(5) P strais oocysts, GII - three dogs infected with 1.0 x 10(6) RH strain tachyzoites, and GIII - four controls dogs. Several clinical parameters were evaluated. IFAT was performed to detect anti-T. gondii antibodies. Presence of the parasite in semen was evaluated by PCR and bioassay techniques. Tissue parasitism was examined using bioassays and immunohistochemistry in testicle and epididymis fragments collected after orchiectomy. In semen samples collected from these two groups, the presence of T. gondii was verified by bioassays and PCR. T. gondii was detected by immunohistochemistry in tissues (testicle and epididymis fragments) of all six experimentally infected dogs. The T. gondii-positive seminal samples were used in the artificial insemination (AI) of four female dogs free of toxoplasmic infection. Seven days after AI, all of the female dogs presented serologic conversion (IFAT). Fetal reabsorption occurred in two of the dogs, while the others sustained full-term gestation. Several T. gondii cysts were detected in the brains of four offspring. These results suggest that T. gondii can be sexually transmitted in domestic dogs. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Dogs; PCR; Semen; Toxoplasma gondii; Transmission by semen